P720 Drug survival of first-line biologics in inflammatory bowel disease: large single-centre experience from UR-CARE. (30th January 2023) - Hanzel, J; Supovec, E; Smrekar, N; Koželj, M; Kurent, T; Štabuc, B; Novak, G; Drobne, D; ,
Abstract: Background: The expanding therapeutic armamentarium for inflammatory bowel disease (IBD) has led to uncertainty about the optimal first-line biological therapy for a given patient. Given the paucity of dedicated head-to-head trials, treatment decisions can be supported by network meta-analyses or real-world data. Our aim was to assess the drug survival of first-line biologics by drug class (anti-tumour necrosis factor [TNF] agents, anti-integrin, anti-interleukin [IL]-12/23) and identify potential predictors for prolonged drug survival in our cohort of IBD patients, supported by the United Registries for Clinical Assessment and Research (UR-CARE). Methods: We prospectively included all adult patients with IBD treated with biological drugs and at least one follow-up visit between October 2021 and August 2022 at our tertiary referral centre. Patient data were collected retrospectively from records and included demographics, disease characteristics and drug survival. Data were collected in UR-CARE with data lock on August 1, 2022. Cox regression was used to assess the association of patient and disease characteristics with drug survival of first-line biologic drugs by drug class. Results: We included 1047 adult patients with IBD (644 Crohn's disease [CD], 403 ulcerative colitis [UC]) (Table 1). Among TNF antagonists, adalimumab was most frequently used in CD (280/644, 43.5%; infliximab: 241/644, 37.4%), infliximab was most frequently used in UC (169/403, 41.9%; adalimumab: 55/403, 13.6%; golimumab: 52/403, 12.9%). Unadjusted median drug survival of the first-line biologic did not differ by medication class in CD, but was significantly longer for vedolizumab than for anti-TNF agents in UC (hazard ratio [HR] for discontinuation 0.585, 95% confidence interval [CI] 0.41–0.84; P = 0.003) (Table 2). Disease duration and extent were not associated with drug survival. In CD, isolated ileal disease was associated with longer drug survival (HR 0.83, 95% CI 0.70–0.99; P = 0.04). Findings for both CD and UC were consistent in a sensitivity analysis of patients (CD 228, UC 202) started on biologics after January 1, 2019 when all three drug classes could be prescribed first line without limitations. Conclusion: In our cohort of 1047 patients with IBD, the drug survival of first-line biologics was comparable regardless of drug class in CD. In UC, first-line vedolizumab was associated with longer drug survival. Disease location and duration did not impact drug survival.